Economic hardships from COVID-19 and its association with socioeconomic factors and diabetes management indicators: A cross-sectional study - Yiqian Xin; Ege K. Duman; Xinyi Yan; Enying Gong; Shangzhi Xiong; Xinyue Chen; Truls Østbye; Lijing L. Yan (Heliyon, 2022)
Aims: The three objectives of this study were to determine the economic hardships of COVID-19 pandemic, their socio-economic predictors, and their association with diabetes management indicators in three cities in a middle-income country. Methods: A community-based cross-sectional survey of 309 people with diabetes aged 34–85 was carried out in 10 communities during July and August 2020. Face-to-face surveys were conducted by trained community physicians. Economic hardship was assessed by income loss and “financial toxicity” during the COVID-19 pandemic, where financial toxicity was defined as experiencing economic difficulties in accessing diabetes management resources. Indicators of diabetes management was assessed by blood glucose and Hemoglobin A1c (HbA1c) monitoring frequency. Results: Among all respondents, 38.5% reported having income loss, and 15.5% experiencing financial toxicity during the pandemic. Younger and self-employed people living suburban areas were more likely to experience income loss. Similarly, suburban area residency and lower household income were associated with financial toxicity. Patients with financial toxicity were less likely to monitor HbA1c in the past three months (OR = 0.20; 95% CI, 0.07–0.48). Conclusion: Diabetes management as indicated by less frequent HbA1c monitoring was associated with experiencing COVID-19 related financial toxicity. Our findings identified vulnerable groups in need of additional support for diabetes management.